2010
DOI: 10.1016/j.neuron.2010.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial Pulsed Ultrasound Stimulates Intact Brain Circuits

Abstract: Electromagnetic-based methods of stimulating brain activity require invasive procedures or have other limitations. Deep-brain stimulation requires surgically implanted electrodes. Transcranial magnetic stimulation does not require surgery, but suffers from low spatial resolution. Optogenetic-based approaches have unrivaled spatial precision, but require genetic manipulation. In search of a potential solution to these limitations, we began investigating the influence of transcranial pulsed ultrasound on neurona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

43
741
7
7

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 836 publications
(798 citation statements)
references
References 64 publications
43
741
7
7
Order By: Relevance
“…It is possible that the significantly delayed expression of BDNF protein along with induced antiapoptotic Bcl2a1 and Birc3 mRNA would have limited the extent of apoptosis and reactive microglia by 24 h postsonication (65,75). It has been reported that low-intensity pFUS without MB used in neuromodulation studies increased BDNF expression by CA1 and CA3 neurons in the hippocampus within 45 min, stimulating neurogenesis and brain plasticity (76).…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the significantly delayed expression of BDNF protein along with induced antiapoptotic Bcl2a1 and Birc3 mRNA would have limited the extent of apoptosis and reactive microglia by 24 h postsonication (65,75). It has been reported that low-intensity pFUS without MB used in neuromodulation studies increased BDNF expression by CA1 and CA3 neurons in the hippocampus within 45 min, stimulating neurogenesis and brain plasticity (76).…”
Section: Discussionmentioning
confidence: 99%
“…Working with cultured mouse hippocampal slices, the team found that ultrasound triggers nerve impulses by activating voltage-gated sodium and calcium channels 3 . In 2010, the researchers showed that ultrasound could remotely stimulate brain cells in the motor cortices of anaesthetized mice 4 . And a few years later, researchers at INSERM -France's biomedical-research agency based in Paris -replicated the effect in brain areas that control eye movements in conscious monkeys 5 .…”
Section: Early Workmentioning
confidence: 99%
“…Tufail et al observed clinical motor contraction following stimulation of the motor cortex of mice, 32 while others have described reversible suppression of visual-evoked potentials using LIFUS. 32 The potential uses of LIFUS not only in neuromodulation but also brain mapping suggest that this is a novel and emerging technology; however, the efficacy and duration of effect of this technique is currently unknown.…”
Section: The Future Of Focused Ultrasound Low-intensity Focused Ultramentioning
confidence: 99%